GENERATING A HIGH QUALITY AND INTEGRITY CAREER JUDGES RECRUITMENT POST-CONSTITUTIONAL COURT DECISION NUMBER 43/PUU-XIII/2015 - Indriati Amarini (Jurnal Dinamika Hukum, 2018)
Recruitment of judges is an instrument to produce high quality and integrity judges. There are some different views related to the authorized institution to carry out career judges recruitment. It makes Indonesian Judges Association (Ikahi) proposes Judicial Review on the involvement of Judicial Commission to the Constitutional Court. The problem is how to implement the recruitment of ca-reer judges after the decision of Constitutional Court Number 43/ PUU-XIII/2015. This is a doctri-nal research. Based on the result of the research, the Constitutional Court Decision has fully man-dated the Supreme Court to recruit first-level judges. It requires an improvement in the career judges re-cruitment by the Supreme Court to be more objective, open, and transparent to obtain a high qual-ity and integrity judges. Keywords: career judges, recruitment, Constitutional Court Decision